Brain regions supporting verbal memory improvement in healthy older subjects - Eliane C. Miotto; Joana B. Balardin; Cary R. Savage; Maria da Graça M. Martin; Marcelo C. Batistuzzo; Edson Amaro Junior; Ricardo Nitrini (Arquivos de Neuro-Psiquiatria)
Despite growing interest in developing cognitive training interventions to minimize the aging cognitive decline process, no studies have attempted to explore which brain regions support the application of semantic strategies during verbal memory encoding. Our aim was to investigate the behavioral performance and brain correlates of these strategies in elderly individuals using fMRI in healthy older subjects. Method Subjects were scanned twice on the same day, before and after, directed instructions to apply semantic strategies during the encoding of word lists. Results Improved memory performance associated to increased semantic strategy application and brain activity in the left inferior and middle and right medial superior prefrontal cortex were found after the directed instructions. There was also reduced activation in areas related to strategy mobilization. Conclusion Improved memory performance in older subjects after the application of semantic strategies was associated with functional brain reorganization involving regions inside and outside the typical memory network.